Silver nanoparticles modified ZnO nanocatalysts for effective degradation of ceftiofur sodium under UV–vis light illumination. (February 2023) - Pugazhenthiran, N.; Sathishkumar, P.; Albormani, Omeer; Murugesan, S.; Kandasamy, M.; Selvaraj, M.; Suresh, S.; Kumar, S. Karthick; Contreras, D.; Váldes, H.; Mangalaraja, R.V.
Abstract: Light-induced photocatalytic degradation of ceftiofur sodium (CFS) has been assessed in the presence of plasmonic zinc oxide nanostructures (ZnONSTs), like, ZnO nanoparticles, ZnO nanorods (ZnONRs) and ZnO nanoflowers (ZnONFs). Silver nanoparticles (Ag NPs) loaded ZnO nanostructures (Ag-ZnONSTs) are obtained through seed-assisted chemical reaction followed by chemical reduction of silver. The surface modification of ZnO nanostructures by Ag NPs effectually altered their optical properties. Further, the surface plasmonic effect of Ag NPs facilitates visible light absorption by ZnONSTs and improved the photogenerated electron and hole separation, which makes the ZnONSTs a more active photocatalyst than TiO2 (P25) nanoparticles. Especially, Ag-ZnONRs showed higher CFS oxidation rate constant (k' = 4.6 × 10 −4  s −1 ) when compared to Ag-ZnONFs (k' = 2.8 × 10 −4  s −1 ) and Ag-ZnONPs (k' = 2.5 × 10 −4  s −1 ), owing to their high aspect ratio (60:1). The unidirectional transport of photogenerated charge carriers on the Ag-ZnONRs may be accountable for the observed high photocatalytic oxidation of CFS. The photocatalytic oxidation of CFS mainly proceeds through OH radicals generated on the Ag-ZnONRs surface under light illumination. In addition, heterogeneous activation of peroxymonosulfate by Ag-ZnONRs accelerates the rate of photocatalytic mineralization of CFS. The quantification of oxidative radicals supports the proposed CFS oxidation mechanism. Stability studies of plasmonic Ag-ZnONSTs strongly suggests that it could be useful to clean large volume of pharmaceutical wastewater under direct solar light irradiation. Graphical abstract: Image 1 Highlights: Ag–ZnO nanorods, nanoflowers & nanoparticles were prepared by solvothermal method. Colorless ceftiofur sodium was mineralized under Ag/ZnO UV–vis light illumination. Ag-ZnONRs exhibited a 4-fold enhancement of CFS oxidation compared to P25 TiO2 NPs. Estimation of . OH radicals was performed to understand rate of CFS oxidation. 89% of CFS was mineralized in presence of Ag–ZnO/PMS at 6 h illumination.